Direct formation of amide-linked C-glycosyl amino acids and peptides via photoredox/nickel dual catalysis - Ye, Xiang-Yu (2024)
Glycoproteins account for numerous biological processes including those associated with diseases and infections. The advancement of glycopeptides has emerged as a promising strategy for unraveling biological pathways and discovering novel medicines. In this arena, a key challenge arises from the absence of efficient synthetic strategies to access glycopeptides and glycoproteins. Here, we present a highly concise approach to bridging saccharides with amino acids and peptides through an amide linkage. Our amide-linked C-glycosyl amino acids and peptides are synthesized through cooperative Ni-catalyzed and photoredox processes. The catalytic process generates a glycosyl radical and an amide carbonyl radical, which subsequently combine to yield the C-glycosyl products. The saccharide reaction partners encompass mono-, di-, and trisaccharides. All 20 natural amino acids, peptides, and their derivatives can efficiently undergo glycosylations with yields ranging from acceptable to high, demonstrating excellent stereoselectivities. As a substantial expansion of applications, we have shown that simple C-glycosyl amino acids can function as versatile building units for constructing C-glycopeptides with intricate spatial complexities.